A Creation of Sculpture in Applied Art: A Case Study of Banana Fiber Paper in Tok Phrom Sub-District, Khlung District, Chanthaburi - Pothong, Kittiya; Camtawee, Kittipol; Rungsiri, Auemporn; Charoenwong, Sitang (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2025)
This research aims to create a new form of innovative applied sculptures using banana stalk paper. Data were collected from the following sample groups: 1) three experts in banana stalk paper products, who are knowledgeable about its history, processes, and product development in various forms; 2) four individuals with expertise and experience in producing banana stalk paper products; 3) one individual with knowledge and understanding of the physical characteristics and environmental context of the Tok Phrom community; 4) two instructors in fields related to art, with expertise in visual arts or applied sculpture; 5) two product designers with experience in designing souvenir products and 6) three experts who responded to questionnaires assessing the appropriateness of the products. The research tools included interviews, focus group discussions, and expert opinion surveys. The data were analyzed using descriptive analysis and mean and percentage values. The results revealed that : the innovative applied sculptures using banana stalk paper could be employed to create products in several ways including: 1)the prototype could be created as a table clock; 2) the design could be aligned with the local identity of the Tok Phrom community, for example, a gem separator; 3) the prototype is a bas-relief sculpture that was evaluated by the experts of its suitability for the applied sculptures for community product development. It had a good level of suitability with a mean of 4.48, or 89.60 percent.